Influence Of Service, Promotion and Price On Sales Car in Pt. Alifindo Sentral Mobil Batam - Sujono, Imam; Ngaliman, Ngaliman (Universitas Batam, 2021)
Sales are the lifeblood of a company, because profit can be obtained. Sales play an important role for trading companies so that the products sold by the company can be sold and provide income for the company. Sales efforts can be seen from the sales volume obtained. In other words, whether the company can make a profit or not is very dependent on the success of sales. The purpose of this study was to determine and analyze the effect of Service, Promotion, and Price on Sales at PT. Alfindo Sentral Mobil Batam. The method used in this research is quantitative method. The population in this study are potential customers of PT. Alfindo Sentral Mobil with a total of 240 people (2022). The sample of this research is 71 respondents. The data collection technique used in this study was a questionnaire or questionnaire which was tested for validity and reliability. The data analysis technique of this research uses Multiple Linear Regression, Classical Assumption Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this study using the SPSS version 23 software program. The results of this study indicate that the service has a positive and significant effect on the sales of PT. Alfindo Sentral Mobil with a probability value of 0.041 < 0.05. Promotion has a positive and insignificant effect on sales of PT. Alfindo Sentral Mobil with a probability value of 0.085 > 0.05. Price has a positive and insignificant effect on sales of PT. Alfindo Sentral Mobil with a probability value of 0.143 > 0.05. The coefficient of determination value of 85.1% shows the contribution of services, promotions, and prices to the sales of PT. Alfindo Sentral Mobil and the remaining 14.9% are explained by various other variables not proposed in this study.